The Practice of Accounting Conservatism by Listed Companies in a Developing Region: A Case Study of the Gulf Co-operating Council (GCC) Region - ASMA JARDAN (2021)
The rise in transparency of businesses, especially those listed on stock exchanges, increases the pressure on board executives to act in a conservative manner and to avoid risky behaviour. These pressures impact on the developed markets (such as the London FTSE exchange and Wall Street in New York) as well as developing markets and regions. The concept of accounting conservatism which is the use of conservative practices by businesses that are shown in the financial reports of the business concerned has gathered increasing interest by stakeholders and regulators. However, developed markets tend to have mature systems that support good governance whereas in the developing regions there is less control and more opportunity for risky behaviours so as to exploit growth of the economies. The academic literature is dominated by studies of developed markets and a gap was identified for a greater understanding of the constraints and context-rich influences on the practice of accounting conservatism by businesses listed on the exchanges of developing countries that are transitioning from rentier economies. This study, using a theory-building approach, was designed to conceptualise accounting conservatism and then to test a literature-derived model in the context of a developing region. The region selected was the GCC stock exchanges and key industrial/commercial sectors within the markets. The model was developed and tested by world-renowned academic and Board-level staff, from developed and developing markets, before being used to test the conformance of businesses listed on the GCC exchanges. The researcher applied the model to multiple sectors in five of the GCC economies and compared and contrasted practices by individual organisations, sectors, and the market itself to test the level of conservativeness in practice. The findings show a significant gap in the body of knowledge concerning the application and practice of accounting conservatism in this developing region. Previous studies have tested only single practices/factors of businesses to determine whether they were conservative or not. The holistic model developed by the researcher shows significant influences from equity stakeholders, Chief Executive and Chief Financial officer tenure, board diversity, gender balancing and the presence of local royal family members on the board and/or as equity holders directly support greater conservatism and are supported by the use of ‘Big 4’ auditors. These findings show a new set of relationships and conditions which support the modern application of the principle of accounting conservatism and differences with the findings of previous studies conducted in developed markets. The conclusions of the study show that the gap in understanding the developing country and market context has been closed through the validity of the model produced and that the model has predictive utility in determining how a company will operate under certain prevailing circumstances. The model can therefore support more traditional measures (formulae) that address quantitative business performance and the model offers many new insights into the practices of listed businesses. The model is offered to the academic community for further testing and to frame subsequent studies in this vital field of study.